Perbedaan Pasar Uang Syariah di Indonesia dengan Kuwait - Adik Tya Hasibuan; Divya Reyvani; Ika Damai Sari; Intan Juwita Damanik; Nurul Syafriani; Putri Yuanita; Maryam Batubara (Lembaga Pengembangan Kinerja Dosen, 2025)
This study examines the fundamental differences between the Islamic money markets in Indonesia and Kuwait in terms of system structure, financial instruments, regulation, and the role of monetary authorities. Indonesia applies a dual banking system where Islamic and conventional systems operate side by side, while Kuwait adopts an integrated system where Islamic instruments are embedded in national monetary policy. Indonesia's instruments are more diverse (e.g., PUAS, SBIS, Sukuk BI), yet face challenges in liquidity and market penetration. In contrast, Kuwait utilizes instruments such as interbank tawarruq and ijarah-based short-term securities, supported by a more mature Islamic financial infrastructure. This study highlights the importance of regulatory support, financial education, and infrastructure enhancement to strengthen the role of Islamic money markets in national financial stability.